Pathogenicity and potential capacity for producing mycotoxins by Fusarium sambucinum and Fusarium solani isolates derived from potato tubers. - Lenc, Leszek (Plant Breeding and Seed Science, 2011)
Studies of potential abilities of F. sambucinum to produce trichothecenes was conducted on isolates previously confirmed as belonging to this species by PCR. In all cases, A positive result for the presence of Tri5 gene, coding the ability to synthesize these mycotoxins. There was no potential to synthesize trichothecenes by F. solani. Further analysis concerned the potential ability of F. sambucinum to produce group B trichothecenes (DON and NIV). No isolate gave the expected amplification product (282 bp for deoxynivalenol and 312 bp for nivalenol), which would indicate the potential for producing these mycotoxins. Studies have shown the ability to produce trichothecenes of group A. Analysis of the potential ability for the synthesis of enniatins by F. sambucinum showed that 91% of isolates gave of 332 bp amplification product, which proves them as potencial producers of these mycotoxins. There were significant differences in the pathogenicity of F. sambucinum and F. solani represented by the size of decay caused by these species. The rotten tissue area caused by F. sambucinum was about 10 times bigger than after inoculation by F. solani. Furthermore, isolates within the same species (F. sambucinum) showed diverse pathogenicity. It should be noted, however, that the concentration of mycotoxins does not depend on the size of rotten tissue of potato tubers. Isolate, which caused the most severe disease symptoms, produced low concentrations of mycotoxins.